A Remotely Delivered Progressive Walking Intervention for Adults With Persistent Symptoms of a Mild Traumatic Brain Injury: Feasibility and Exploration of Its Impact - Alarie, Christophe; Gagnon, Isabelle; Guise, Elaine de; McKerral, Michelle; Kersalé, Marietta; Hoog, Béatrice van het; Swaine, Bonnie (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Persistent post-concussion symptoms following a mild traumatic brain injury (mTBI) can impact function and participation of adults. Physical activity is recommended to reduce symptoms and foster return to normal activities. Adults with a mTBI may have personal factors or experience accessibility issues restricting physical activity. Walking is a physical activity accessible to most that could be delivered remotely. Objectives: Determine the feasibility, safety, and acceptability of a remotely delivered progressive walking intervention designed for adults with persistent mTBI symptoms and explore its effects on health-related outcomes. Methodology: This feasibility study using a single-group pre-post mixed methods convergent parallel design was conducted remotely. Adults aged 18-65 years with a mTBI reporting persistent symptoms for ≥3 months were recruited. The 8-week remote progressive walking intervention aimed to increase the weekly number of steps walked by 40% based on a 1-week baseline measured by a Fitbit Inspire 2 activity monitor. Feasibility measures were about the intervention, its remote delivery, safety, and acceptability. Health-related outcomes were post-concussion symptoms, kinesiophobia, mood, sleep, fatigue, and quality of life. Semi-structured exit interviews were recorded and transcribed verbatim. Quantitative and qualitative data were analyzed separately, and results merged, compared, and contrasted. Descriptive statistics and paired samples t-tests were used. The qualitative analyses followed an iterative content analysis approach using reflexivity and triangulation of sources. Results: Twenty adults (16 women) aged 42.5±11.51 years with persisting symptoms for 9.25±6.43 months participated, adhered to 94.38% of sessions, completed the intervention, and found it to be feasible, safe and acceptable. Participants increased weekly total number of steps walked (change=14,886±18,283; t=3.55, p=0.003). Severity of post-concussion symptoms (change=-6.42±10.69; t=-2.62, p=0.01), kinesiophobia (change=-5.0±6.86; t=3.18, p=0.005), anxiety (change=-1.53±3.01; t=-2.21, p=0.04), and fatigue (change=-10.21±10.20; t=-4.37, p=0.0005) were reduced, whilst quality of life improved (change=10.58±13.35; t=3.46, p=0.002). Participants' perceptions corroborate most quantitative results; they felt improved self-efficacy about physical activity and provided five key recommendations. Discussion: This study demonstrates the feasibility, safety, and acceptability of the remote 8-week progressive walking intervention, a promising approach to reduce persisting symptoms, improve physical activity level health-related outcomes and quality of life of adults with persistent post-concussion symptoms following a mTBI.